DESCRIPTION OF PARENTS' KNOWLEDGE LEVEL ABOUT WORMS IN PRE-SCHOOL CHILDREN TUNAS MULIA KINDERGARTEN - Rahmadhani, Audhyra; Sulystiono, Dony (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2023)
Worm infestation is still a serious problem in Indonesia. Worm infestation is often considered a trivial disease by most people. In this case this disease can reduce the level of health of children e.g. anemia, growth and development disorders, cognitive development disorders, lazy activities and weight gain, The research design used in this research is